The Essential Guide for Competent Teaching Assistants : Meeting the National Occupational Standards at level 2 - Watkinson, Anne.; Bickmore, Margaret; Roper, Ian. (London : David Fulton, 2003)
This book provides the underpinning knowledge to support teaching assistants in all phases of schooling when undertaking study at a basic level. In contains practical examples of work, and ideas to try out.
Includes bibliographical references (p. 143-145) and index.
Keywords: Teachers' assistants -- Great Britain; Education